Family-centered care for a patient with multiple organ dysfunction syndrome in the intensive care unit: A case report - Darmawulan, Nurul; Emaliyawati, Etika; Lin, Chiao Ling (The Journal of Palembang Nursing Studies, 2023)
Background: Patients with multiple organ dysfunction syndrome (MODS) require complex intensive care, and family involvement plays an essential role in achieving patient recovery. Family-centered care in the intensive care unit (ICU) benefits patients, families, and healthcare workers. Objective: This case study aimed to evaluate the family-centered care approach for patients with MODS in the ICU. Case: A 46-year-old male patient with MODS presented various problems, including the risk of respiratory infections, impaired renal perfusion, and pressure sores. An interview with the patient’s family revealed that they felt guilty, worried, and lacked sufficient information about the patient’s condition. The interventions provided to the family included giving them information about the patient’s condition, care plans, and evaluation results after procedures, providing spiritual guidance, offering family support, and involving them in the patient’s required procedures.  Conclusion: After the patient had been admitted for two days, there was an improvement in the patient’s outcomes. Simultaneously, the patient’s family experienced a sense of calmness and increased satisfaction with the provided health services. To facilitate the implementation of family-centered care in the ICU, it is crucial to further develop hospital policies. Moreover, achieving successful family-centered care necessitates the support and cooperation of the medical staff.